DNA-Based Nanostructured Platforms as Drug Delivery Systems - Kumar M.; Jha A.; Mishra B. (My University, 2025)
DNA nanotechnology has recently provided a novel approach for developing safe, biocompatible, biodegradable, non-immunogenic, and non-toxic drug delivery systems. DNA nanostructures have numerous advantages for deployment as drug delivery platforms, owing to programmable assembly, ease of production, reproducibility, and precise control over size, shape, and function. DNA nanostructures can dramatically improve the delivery of poorly soluble drugs, decreasing cytotoxicity to normal tissues and improving therapeutic effectiveness. Using different conjugation methods, DNA nanostructures can be precisely integrated with a wide range of functional moieties, including proteins, peptides, aptamers, polymers, lipids, inorganic nanoparticles, and targeting groups, to enhance the nanostructure stability, extend circulation, and specify drug delivery. Smart DNA nanostructures with targeting ligands or a stimuli-responsive moiety specify therapeutic delivery to target, minimize drug loss attributable to prior drug release or off-target distribution, improve target accumulation, promote cellular internalization, bypass efflux pumps, and avoid adverse effects. Target-specific delivery by smart DNA nanostructures, in turn, maximizes drug concentration, reaching the target locations at a faster rate and preventing therapeutic failure while also lowering the dose needed for therapeutic effect. This Review provides an overview of DNA nanostructures for drug encapsulation and selective delivery to the desired sites. DNA nanostructures are a novel platform for drug delivery with improved performance that may be used to treat a variety of diseases. © 2024 The Authors. Co-published by Zhejiang University and American Chemical Society.